Pemenuhan Upah Layak Bagi Pekerja Melalui Penetapan Upah Minimum Pasca Berlakunya Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja Menjadi Undang-Undang - Ambarita, Hendra Halomoan; Hartati, Hartati; Yetniwati, Yetniwati; Yanti, Herma (Universitas Batanghari Jambi, 2024)
The government has regulated the fulfillment of living wages for workers through the Job Creation Law and Government Regulation Number 51 of 2023 concerning Amendments to Government Regulation Number 36 of 2021 concerning Wages. A living wage is a basic right of workers/laborers that must be fulfilled by employers. The method in this research is that this research is descriptive analysis with the type of research, namely iordischromatid, which uses data sources, namely primary legal materials, secondary legal materials and tertiary materials and the data analysis used is qualitative analysis. The results of this research are that a living wage is a wage that can adequately meet the minimum living needs of workers/laborers and their families. The Job Creation Law and Government Regulation Number 51 of 2023 concerning Amendments to Government Regulation Number 36 of 2021 concerning Wages are regulations that regulate the fulfillment of living wages for workers/laborers. The Job Creation Law mandates that the government establish wage policies as an effort to realize the rights of workers/laborers to a living that is worthy of humanity. This policy includes setting a minimum wage every year. Government Regulation Number 51 of 2023 concerning Amendments to Government Regulation Number 36 of 2021 concerning Wages regulates the formula for calculating minimum wages which includes three variables, namely inflation, economic growth and a certain index (symbolized in the form a). The minimum wage calculation formula regulated in Government Regulation Number 51 of 2023 concerning Amendments to Government Regulation Number 36 of 2021 concerning Wages is expected to encourage an increase in people's purchasing power and realize a living wage for workers/laborers. However, periodic evaluations need to be carried out to ensure that the formula can adequately meet the minimum living needs of workers/laborers and their families.